THE MAINTENANCE OF BAHASA JAWA - NENENG SRI LESTARI (The Seall Journal, 2021)
This study deals with the maintenance of bahasa Jawa in Langkat. It employs qualitative research design. This study aims to describe the maintenance of Bahasa Jawa in Langkat. The subjects were twenty Javanese speakers in Langkat. The instruments used for this study were observation, questionnaire, and interview (in-depth interview). The observation was applied to get the data about the Javanese speakers in maintaining their language such what the language that they used in daily communication. Questionnaire was applied to collect the data about the factors which support Bahasa Jawa maintenance in Langkat and interview was applied to get data about the reason of Javanese to maintain their language and to get in depht result of the research. The data was analyzed by using Miles and Huberman’s data analysis. Bahasa Jawa is maintained in Langkat. They keep using their language (Bahasa Jawa) in Langkat because they realize the condition of Bahasa Jawa nowdays, whereas there were some of them shift from Bahasa Jawa maintenance. They are living in an area dominated by Javanese, visiting homeland regularly, intra marriage, use of the language in family domain, use of the language in neighborhood domain, use of the language in workplace domain, use the language in education domain, ethno linguistic vitality, use of the languge in religion domain, practice of adat istiadat (traditional) ceremony and solidarity of Javanese to use their language together. Bahasa Jawa keep maintain and exist in Langkat.